Legume establishment in pangolagrass pastures in the humid tropics - Bryan, William B.; Velásquez, Efrain R. (International Center for Tropical Agriculture, 1982)
An experiment to compare two methods for establishing different forage legumes in a pangolagrass (Digitaria decumbens) pasture, was carried out on a loamy clay soil in the Orinoco Delta, Venezuela. Fourteen legumes, including Centrosema plumieri and three cultivars of Stylosanthes guianensis, were hand seeded into clipped pasture that had been either disk harrowed or rotovated twice and disk harroved. Establishment of the legumes and recovery of the grass were observed over a 4 1/2-month period. Six harvests were then made at six-week intervals, and the dry matter (DM) yield and the percentage crude protein (CP) of the pastures were determined. Legumes with a climbing growth habit established more quickly where only the disk was used. All legume/pangolagrass associations yielded more DM and CP than grass only. Plots with C. plumieri or S. guianensis gave double the DM yield and triple the CP yield of grass only. The maximum DM yield of 1.8 metric tons/ha per 6 wks was produced by an S. guianensis/pangolagrass association which produced 0.33 metric tons of CP/ha per 6 wks. The majority of the plots had 30-50 percent legume. All legumes increased the CP content of the associated pangolagrass. Pangolagrass growing with C. plumieri contained 14.7 percent CP compared to 10.7 percent when grown alone.